A Bibliometric Study of Internal Audit Research Development - Loso Judijanto; Ni Ketut Sukanti (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the development of internal audit research through a comprehensive bibliometric approach. Using data collected from the Scopus database covering the period 2000–2026, this research examines publication trends, influential authors, leading countries, and the conceptual structure of the field. Bibliometric techniques, including co-authorship analysis, citation analysis, keyword co-occurrence, overlay visualization, and density mapping, were conducted using VOSviewer. The results indicate that internal audit research has experienced significant growth and increasing global collaboration, with dominant contributions from developed countries such as the United States and the United Kingdom. The intellectual structure of the field is centered on traditional themes such as internal control, auditing, and risk management, while emerging topics such as digital transformation, artificial intelligence, and sustainability are gaining prominence. The findings also reveal that internal audit research is becoming more interdisciplinary, extending into areas such as healthcare and environmental governance. This study contributes by providing a structured overview of the knowledge landscape and identifying research gaps, particularly in technology integration and sustainability practices. The results are expected to guide future research directions and support the advancement of internal audit practices in a rapidly evolving business environment.